Climatic evolution of the central equatorial Pacific since the Last Glacial Maximum. (27th August 2016) - Seo, Inah; Lee, Yuri; Lee, Yong Il; Yoo, Chan Min; Hyeong, Kiseong
Abstract: This paper investigates paleoceanographic changes at a central equatorial Pacific site (6°40′N, 177°28′W) since the last glacial maximum using planktic foraminifera assemblages, together with the oxygen isotope (δ 18 O) and Mg/Ca compositions of three species ( Globigerinoides sacculifer, Pulleniatina obliquiloculata, and Globorotalia tumida ) that dwell in the mixed layer, upper thermocline, and lower thermocline, respectively. While the Mg/Ca‐derived temperatures of the mixed layer and lower thermocline varied within a narrow range from 18 ka onward, the upper thermocline temperature increased by as much as 3°C during the last deglaciation (18–12 ka) with a simultaneous decrease of δ 18 O. These changes are best explained by an enhanced mixing of the upper ocean and a reduced habitat depth separation between P. obliquiloculata and G. sacculifer during the 18–12 ka interval. The planktic foraminifera assemblage during the same period resembles modern composition at subtropical central Pacific sites that are strongly influenced by the northeasterly Trades and North Equatorial Current (NEC). We suggest that the study site, presently under the control of the Intertropical Convergence Zone (ITCZ)‐North Equatorial Countercurrent, had been influenced by the northeasterly Trades and NEC during the 18–12 ka interval. This interpretation is consistent with previous documentation of a more southerly location of the ITCZ during two Northern Hemisphere cooling events; the Heinrich Stadial 1 and the Younger Dryas, and implies that the mean annual position of the ITCZ was located south of the study site, by at least 2° of latitude. Key Points: Planktic foraminifera reveal oceanographic changes in central equatorial Pacific since the LGM The NEC region had expanded equatorward by strengthening of NE Trades during the last deglaciation The ITCZ had moved southward at least 2° during the last deglaciation in the central Pacific